The Course of Diabetic Foot Infection in Elderly Patients: Data of Patients From Turkey - Balin, Safak Ozer; Asan, Mehmet Ali; Ozcan, Erhan Cahit; Ugur, Kader; Senol, Arzu (Sage Publications Inc, 2025)
With the aging population, it is expected that diabetes and related complications will increase rapidly. The aim of this study was to examine the signs and symptoms of diabetic foot infection in elderly individuals. Patients with diabetic foot infection were grouped as mild, moderate, and severe. Patients aged <65 years and those who did not meet the diagnosis of diabetic foot infection were excluded from the study. Only the first applications of patients who applied to the hospital multiple times with diabetic foot infection diagnosis were evaluated. 314 patients were included in the study. The mean age of the patients was 71.5 (+/- 12). The number of patients aged 75 and over was 125 (39.8%). Of the patients, 25.7% had mild, 61.7% moderate, and 12.4% severe clinical forms. 131 (41.7%) of the patients had osteomyelitis. Amputation was performed in 112 of the patients. Antibiotic treatment was given to 102 patients only. While 89 patients died, a significant correlation was found between all groups between amputation rate and mortality frequency and clinical severity of diabetic foot infection (P < .001). In our study, it was observed that the clinical severity of diabetic foot infection was more severe and the overall mortality rate was higher in geriatric patients. In light of all these data, it can be concluded that an early and comprehensive roadmap should be followed in geriatric patients with diabetic foot infection who have an increased risk of morbidity and mortality.
Keywords: diabetic foot; geriatrics; Infections; prognosis